2010
DOI: 10.1094/pdis-04-10-0255
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Fusarium oxysporum f. sp. lycopersici Races in Tomato in Sinaloa, Mexico

Abstract: Sinaloa State is the main producer of tomatoes (Solanum lycopersicum L) in Mexico where production attained 15,784 ha in 2008 (3). Fusarium wilt of tomato caused by Fusarium oxysporum f. sp. lycopersici (Sacc) Snyder & Hansen causes significant yield losses in Sinaloa each year (2). Three pathotypes or races of F. oxysporum f. sp. lycopersici have been described: races 1, 2, and 3 (1). The purpose of this study was to determine the races of F. oxysporum f. sp. lycopersici present in Sinaloa and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Besides, new races of the mentioned pathogen (e.g., race 3) have emerged that can overcome host resistance (Reis et al, 2005). The symptoms of Fusarium wilt disease caused by race 3 are yellowing the lower leaves, vascular necrosis, epinasty, defoliation, plant stunting and ultimately plant death (Sanchez-Pena et al, 2010). Biological control of this pathogen has been the subject of many studies (Ben Abdallah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, new races of the mentioned pathogen (e.g., race 3) have emerged that can overcome host resistance (Reis et al, 2005). The symptoms of Fusarium wilt disease caused by race 3 are yellowing the lower leaves, vascular necrosis, epinasty, defoliation, plant stunting and ultimately plant death (Sanchez-Pena et al, 2010). Biological control of this pathogen has been the subject of many studies (Ben Abdallah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated the presence of only 2 and 3 races on the grounds discussed in San Luis Potosí. Ortega (2010) and Sánchez-Peña et al (2010) also reported the presence of races 2 and 3 of Fol in the state of Morelos and Sinaloa, respectively.…”
Section: Variedades Diferencialesmentioning
confidence: 96%
“…For data analysis, the presence or absence of an allele at a particular locus was scored as 1 and 0, respectively, and the pairwise distance among the strains was calculated from the binary matrix using the Jaccard's coefficient. The resulting distance matrices were used to cluster the strains by the UPGMA (Unweighted Pair Group method using arithmetic means) method using NTSYSpc version 2.0 (Rohlf 1997).…”
Section: Genetic Diversity Among F Oxysporum Isolatesmentioning
confidence: 99%